Sovereign Risk, Fiscal Policy, and Macroeconomic Stability - Kuester, Keith (IMF Working Papers; Working Paper ;, 2012)
This paper analyzes the impact of strained government finances on macroeconomic stability and the transmission of fiscal policy. Using a variant of the model by Curdia and Woodford (2009), we study a "sovereign risk channel" through which sovereign default risk raises funding costs in the private sector. If monetary policy is constrained, the sovereign risk channel exacerbates indeterminacy problems: private-sector beliefs of a weakening economy may become self-fulfilling. In addition, sovereign risk amplifies the effects of negative cyclical shocks. Under those conditions, fiscal retrenchment can help curtail the risk of macroeconomic instability and, in extreme cases, even stimulate economic activity.